Transcranial magnetic stimulation associated with manual therapy in patients with knee osteoarthritis: a randomized controlled clinical trial protocol - Mendonça, Mannaly; Araújo, Maria das Graças; Fonseca, Camilla; Mèlo, Maíra Lima, Luiz; Rocha, Sérgio; Guerino, Marcelo; Lima, Ana Paula; Monte-Silva, Kátia (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Persistent pain in knee osteoarthritis (KOA) may generate sensitization of the afferent and central nervous system (CNS) pathways over time. Therefore, for patients with chronic pain derived from KOA, to associate therapies that address peripheral impairment, such as central and manual therapy and transcranial magnetic stimulation seems to be a promising strategy for pain reduction. Objectives: The purpose of this study is to unite rTMS and TM to control the pain of patients with knee OA and to examine the efficacy of this treatment protocol, assuming that this union would be more beneficial than the formally applied therapies isolated. Methods: This clinical trial with three arms interventions, controlled, triple blind and randomized, will allocate patients with KOA in groups (i) transcranial magnetic stimulation; (ii) sham transcranial magnetic stimulation + manual therapy and (iii) transcranial magnetic stimulation + manual therapy. Pain assessment will be performed using the visual analog scale of pain of 100 points, before and after the interventions, and for a maximum of 30 days after the single session. This session will involve the application of real or fictitious transcranial magnetic stimulation followed by manual or home therapy. Discussion: The study is in the recruitment stage and it is expected that after the application of the therapeutic protocol the group that performed the association has a more significant improvement in comparison to the others. Study registry: The protocol of this study was published on the Clinical Trials (www.clinicaltrials.org), with the registration number NCT03076294.